SIGNS OF MUTUAL DIFFERENCES OF THE TRANSACTION AND CONTRACT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article provides a clear and comprehensive explanation of commodities and contracts, their different aspects, legal characteristics and forms, as well as clearly defining and distinguishing objects that are subject to contractual relations.